Penguatan Literasi Sosial Siswa SD melalui Inovasi Pembelajaran IPS - Nur Haizah Aopmonaim (Jurnal Kajian Pendidikan dan Cakrawala Pembelajaran, 2025)
Social Studies (IPS) learning in Elementary Schools has a strategic role in shaping students' character and social literacy skills. However, the reality in the field shows that IPS learning is often delivered monotonously, with minimal innovation, and is less contextual to students' daily lives. This article aims to examine in depth how innovation in IPS learning can strengthen elementary school students' social literacy based on various relevant literature. Through a literature study approach, this article examines various innovative models, methods, and media that have been applied in IPS learning and their impact on the development of students' social literacy skills. The results of the study show that the use of a contextual approach, project-based learning models, the use of digital media, and the integration of character values ​​can increase social sensitivity, the ability to work together, and understanding of the social environment. These findings indicate that IPS learning is not only a means of transferring knowledge, but also a tool to form young citizens who are socially literate and care about others. This study recommends the importance of teacher training, the development of innovative teaching tools, and collaboration between schools and the community to realize effective strengthening of social literacy in elementary schools.